Digital media’s role in overcoming anxiety, enhancing linguistic elements and fostering motivation for developing speaking skills - Syamsudin, Syamsudin; Budianto, Langgeng; Prihadi, Kususanto Ditto; Susanto, Djoko; Rohman, Abdul; Kholil, Ahmad; Firdousi, Muhammad Anwar (International Journal of Evaluation and Research in Education (IJERE), 2025)
The qualitative study investigated the digital media impact on language learning, focusing on overcoming anxiety, enhancing linguistic elements, and fostering motivation for developing speaking skills among four English as foreign language (EFL) learners at an Islamic University in Malang, Indonesia. Through the use of observations and in-depth interviews, the study found that learners utilized various digital media such as storytelling, movies, variety shows, and song videos to aid their speaking learning process. The findings indicated that digital media played a significant role in helping learners overcome language anxiety by providing a platform for practice without direct peer interaction, thereby reducing feelings of fear and shyness. Additionally, digital media usage contributed to linguistic element enhancement, including vocabulary, pronunciation, grammar, and speaking fluency. Moreover, learners’ motivation for developing speaking skills was positively influenced by the enjoyment derived from using digital media which increased their willingness to practice speaking. The study underscores the importance of integrating digital media into EFL speaking instruction due to its potential to address language anxiety, improve linguistic elements, and foster motivation for speaking ability development. By leveraging digital media tools effectively, educators can create engaging and supportive learning milieus that provide to the diverse needs of language learners, eventually enhancing learners’ speaking skills.